1983
DOI: 10.2134/agronj1983.00021962007500020035x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Box‐Cox Transformation Technique for Fitting Crop Yield Trends

Abstract: There is a need for a more general approach to selecting appropriate models for transformation of long‐term crop yield data prior to statistical analysis without a priori restrictions about the mathematical form of the model. A least restrictive formulation about the functional specification of a model is less likely to lead to erroneous results. The objective of the study is to illustrate a general approach to model selection via application of the Box‐Cox transformation technique to estimate national yield t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1992
1992

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…2 • This was further generalized by Boylan et al (1982). Lin & Huang (1983)estimated the generalized functional form for the yield trend of wheat, corn and soybean. Newman (1977) estimated the relationship between the incidence of malaria and the mortality rate and concluded that the functional specificiation obtained by using the Box-Cox procedure was superior to earlier specifications.…”
Section: Hypothesis Tests and Other Inferences On The Transformation mentioning
confidence: 99%
“…2 • This was further generalized by Boylan et al (1982). Lin & Huang (1983)estimated the generalized functional form for the yield trend of wheat, corn and soybean. Newman (1977) estimated the relationship between the incidence of malaria and the mortality rate and concluded that the functional specificiation obtained by using the Box-Cox procedure was superior to earlier specifications.…”
Section: Hypothesis Tests and Other Inferences On The Transformation mentioning
confidence: 99%